2014
DOI: 10.1128/iai.01289-13
|View full text |Cite
|
Sign up to set email alerts
|

The Core Promoter of the Capsule Operon of Streptococcus pneumoniae Is Necessary for Colonization and Invasive Disease

Abstract: Streptococcus pneumoniae is a commensal of the human nasopharynx but can cause invasive diseases, including otitis media, pneumonia, sepsis, and meningitis. The capsular polysaccharide (capsule) is a critical virulence factor required for both asymptomatic colonization and invasive disease, yet the expression level is different in each anatomical site. During colonization, reduced levels of capsule promote binding to the host epithelium and biofilm formation, while during systemic infection, increased capsule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 54 publications
(82 reference statements)
6
76
0
Order By: Relevance
“…The presence of such regulation is reflected by the observation of phase variation of pneumococci (8,54), and studies suggest that little capsule is produced when pneumococci are in contact with the epithelial cell layer (52). However, the mode of regulation remains to be further unraveled, and a number of genes and environmental factors seem to be important (45,(54)(55)(56)(57). The imaging tools used in this work will pave the way for new types of experiments which will help further our knowledge on the pathogenesis of the pneumococcus.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such regulation is reflected by the observation of phase variation of pneumococci (8,54), and studies suggest that little capsule is produced when pneumococci are in contact with the epithelial cell layer (52). However, the mode of regulation remains to be further unraveled, and a number of genes and environmental factors seem to be important (45,(54)(55)(56)(57). The imaging tools used in this work will pave the way for new types of experiments which will help further our knowledge on the pathogenesis of the pneumococcus.…”
Section: Discussionmentioning
confidence: 99%
“…As a positive control for cotranscription, the intergenic region of the previously characterized SPD2018-cbpA operon (52) was also amplified with primers Pr8105 and Pr8106. The mRNA level of the cps locus was quantified by quantitative RT-PCR (qRT-PCR) as described previously (40). Primer pairs Pr7705/Pr7706 and Pr7707/Pr7708 were used to amplify cps2A and cps2E, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Shainheit et al showed that the sequence between the Ϫ35 promoter motif and the transcription start site of the cps locus in the type 4 strain TIGR4 is essential for the transcription of the cps gene cluster (40). There is extensive sequence diversity upstream of the transcription start sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations